Pengaruh Kegiatan Konservasi Lahan Pada Kegiatan Countermeasure For Sediment in Wonogiri Multipurpose DAM Terhadap Laju Erosi Lahan di Bendungan Wonogiri - Dian Swastika; Dyah Wulandari; Sriyana Sriyana; Rifki Maulana (Jurnal Serambi Engineering, 2023)
Sedimentation is one of the main problems in the operation and maintenance of the reservoir because it can cause a decrease in the function of the reservoir, as well as in the Wonogiri reservoir which has been operating since 1982. The JICA Study Team in 2007 calculated the annual erosion production on-farm (land) and off-farm (physical buildings) that occurred in all watersheds flowing into the Wonogiri Multipurpose Reservoir amounting to 17,279 million tons per year. The JICA Study Team carried out the community-based watershed conservation physical activities in the context of implementing the Countermeasure for Sediment in Wonogiri Multipurpose Dam Reservoir (CSWMDR) Program, divided into 2 work programs, namely JICA Slice I (in 2015) and JICA Slice II aims to obtain the rate of erosion and erosion reduction with achievements in accordance with the targets set in the Implementation Plan. This study aims to analyze the rate of erosion in the present and future conditions and land erosion reduction in CSWMDR conservation activities to overcome sedimentation in the Wonogiri Reservoir to support the JICA Slice II work program using the USLE method as well as ArcGIS Software assistance and additional tools Spatial Analyst and Model Builder. The results of the analysis show that the total erosion rate in 10 target villages in the present condition is 158,809.21 m3/year, while the total erosion rate in the future condition is 110,354.92 m3/year, and the total erosion rate reduction is 16,268.27 m3/year.